A method for preparing coal-based hard carbon material
Through the mixed reaction of modified solution and modified coal powder raw materials, optimize the pore structure of coal raw materials, solve the problem of poor conductivity of hard charcoal materials in the existing technology, and realize the high electrical performance and preparation stability of hard charcoal materials Essence
Patent Information
- Application Number
- CN202411554624.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-04
AI Technical Summary
During the preparation process of existing coal-based hard carbon materials, the pore structure of hard carbon is affected due to the direct addition of carbohydrates, which affects the adsorption and embedding efficiency of lithium ions, thereby affecting the conductive properties of hard carbon materials.
Through the use of modified solutions, the modified solution reacts with corn starch to react with corn starch to obtain modified or cluttonic acid. , And get coal -based hard charcoal materials through sintering, annealing and carbonization treatment.
Effectively improve the conductive performance and preparation stability of hard charcoal materials, reduce the transmission path of ions, and reduce the resistance of ion migration.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hard carbon materials, and in particular to a method for preparing a coal-based hard carbon material. Background Art
[0002] Coal-based hard carbon material is a carbon material prepared by specific physical and chemical treatment methods using coal as the main raw material. Hard carbon is widely used in lithium-ion battery negative electrode materials due to its high rate, low temperature resistance and long cycle characteristics.
[0003] In the prior art, during the preparation of coal-based hard carbon, carbohydrates need to be used to produce a cross-linking reaction with the coal raw material to maintain the structural stability of the material. However, during the preparation process, the high temperature environment is used, and the direct addition of carbohydrates will affect the pore structure of the hard carbon, affecting the adsorption and embedding efficiency of lithium ions, thereby affecting the conductive properties of the hard carbon material. Based on this, the present invention provides a method for preparing a coal-based hard carbon material. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a coal-based hard carbon material. The hard carbon prepared by the present invention has good electrical conductivity and preparation stability.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a coal-based hard carbon material, comprising the following steps:
[0006] S1: After processing the coal raw material, a modified coal powder raw material is obtained;
[0007] S2: preparing a modified solution and setting it aside for use after the preparation is completed;
[0008] S3: mixing the modified coal powder raw material obtained by pretreatment in step S1 with the modified solution prepared in step S2, and obtaining a precursor after a mixing reaction;
[0009] S4: cross-linking the precursor obtained in step S3 with carbohydrates, obtaining an intermediate after sintering and annealing, and preparing a coal-based hard carbon material after the intermediate undergoes a first carbonization treatment, a curing treatment and a second carbonization treatment.
[0010] Preferably, the processing of the modified coal powder raw material in step S1 comprises the following steps:
[0011] Step 1: Wash the coal raw material with water to obtain low-ash coal raw material, and then flatten and dry it after washing;
[0012] Step 2: After washing, the large coal raw materials are put into a jaw crusher for preliminary crushing. The coal raw materials after preliminary crushing are screened and crushed repeatedly, and then put into an impact crusher for fine crushing. Finally, they are crushed and screened to obtain coal powder with a particle size of less than 70 μm.
[0013] Step 3: Mix anhydrous ethanol and deionized water in a mass ratio of 1:2.5-3, add 15-20% by mass of coal powder and 3-5% by mass of methacryloyloxy functional silane to the mixed liquid, put the solid-liquid mixture into a magnetic stirrer, and stir it at a speed of 1200-1300r / min for 2-2.5min. After stirring, filter, wash and dry the slurry to obtain a filter cake, crush the filter cake, and screen it to obtain a modified coal powder raw material.
[0014] Preferably, the modified solution preparation method in step S2 is as follows: the modified solution raw materials are composed of the following raw materials in parts by weight: 8-10 parts of deionized water, 5-7 parts of modified maleic acid, 4-6 parts of epoxy emulsifier, 4-6 parts of polyetherimide and 2-3 parts of McBride's acid ethanol solution;
[0015] (1) Weigh deionized water and modified maleic acid as needed, mix them, and keep stirring in a water bath at 60-70°C. After stirring and dissolving in the water bath, a first solution is obtained. Weigh the epoxy emulsifier and add it to the first solution. After continuous stirring for 4-6 minutes, a second solution is obtained.
[0016] (2) Weigh the polyetherimide and McLaughlin's acid ethanol solution as needed and place them in a water bath at 80-90°C for 1-1.5 hours. After the water bath is completed, add the first dissolving solution and the second dissolving solution, stir and react at room temperature for 10-15 minutes, and perform ultrasonic vibration to remove bubbles to obtain a modified solution.
[0017] Preferably, the preparation method of the modified maleic acid is as follows: water and corn starch are mixed in a mass ratio of 1:0.2-0.3 and added to a flask, and a slurry is obtained after stirring for 2-3 minutes, a catalyst is added, and the stirring reaction is continued for 4-5 minutes, and after the stirring reaction is completed, the temperature is raised to 60-65°C and kept warm for 1-1.5 hours, and after the insulation reaction, a terminator accounting for 1-1.5% by mass is added dropwise, and then maleic acid accounting for 5-7% by mass is added, and the temperature is raised to 70-75°C, and the insulation reaction is carried out for 2-2.5 hours, and an equal amount of water in the above steps is added, and the reaction is stirred at room temperature for 2-3 minutes to obtain the modified maleic acid.
[0018] Preferably, the catalyst is one or more combinations of manganese sulfate, cuprous bromide, and manganese dioxide, and the terminator is any one of p-benzoquinone and tetrachlorobenzoquinone.
[0019] Preferably, the cross-linking reaction temperature of the precursor and carbohydrate is 200-300°C, the reaction time is 2-10h, and the sintering annealing temperature is 400-550°C.
[0020] Preferably, the temperature of the first carbonization treatment in step S4 is 800-1100°C, the heating rate is 2-5°C / min, and the heat preservation time is 2-3h.
[0021] Preferably, the curing treatment temperature in step S4 is 1000-1300°C, the heating rate is 30-40°C / min, and the insulation time is 1-1.5h.
[0022] Preferably, the temperature of the second carbonization treatment in step S4 is 1200-1600°C, the heating rate is 6-10°C / min, and the insulation time is 3-5h.
[0023] Furthermore, a coal-based hard carbon material is prepared by the preparation method of the coal-based hard carbon material.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The present invention uses a modified solution. The modified solution is obtained by reacting maleic acid with corn starch as main raw materials to obtain modified maleic acid. The modified solution is pre-mixed with a modified coal powder raw material for reaction. The pore structure of the coal raw material is optimized by the modified solution. The optimized pore structure can reduce the transmission path of ions, thereby reducing the resistance to ion migration, and effectively improving the conductivity of the hard carbon material.
[0026] 2. The present invention modifies the coal raw material so that the impurities attached to the surface of the coal powder as the main added raw material are less, thereby reducing the waste slag generated during the high-temperature preparation process, avoiding the impact of waste slag on temperature control during the carbonization process, and improving the stability of the preparation performance of the hard carbon material. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] Embodiment 1
[0029] A method for preparing a coal-based hard carbon material comprises the following steps:
[0030] S1: After processing the coal raw material, a modified coal powder raw material is obtained;
[0031] S2: preparing a modified solution and setting it aside for use after the preparation is completed;
[0032] S3: mixing the modified coal powder raw material obtained by pretreatment in step S1 with the modified solution prepared in step S2, and obtaining a precursor after a mixing reaction;
[0033] S4: cross-linking the precursor obtained in step S3 with carbohydrates, obtaining an intermediate after sintering and annealing, and preparing a coal-based hard carbon material after the intermediate undergoes a first carbonization treatment, a curing treatment and a second carbonization treatment.
[0034] First, the treatment of the modified coal powder raw material in step S1 includes the following steps:
[0035] Step 1: Wash the coal raw material with water to obtain low-ash coal raw material, and then flatten and dry it after washing;
[0036] Step 2: After washing, the large coal raw materials are put into a jaw crusher for preliminary crushing. The coal raw materials after preliminary crushing are screened and crushed repeatedly, and then put into an impact crusher for fine crushing. Finally, they are crushed and screened to obtain coal powder with a particle size of less than 70 μm.
[0037] Step 3: Mix anhydrous ethanol and deionized water in a mass ratio of 1:2.5, add 15% by mass of coal powder and 3% by mass of methacryloyloxy functional silane to the mixed liquid, put the solid-liquid mixture into a magnetic stirrer, and stir at a speed of 1200r / min for 2 minutes. After stirring, filter, wash and dry the slurry to obtain a filter cake, crush the filter cake, and screen it to obtain a modified coal powder raw material.
[0038] The modified solution preparation method in step S2 is as follows: the modified solution raw materials are composed of the following raw materials in parts by weight: 8 parts of deionized water, 5 parts of modified maleic acid, 4 parts of epoxy emulsifier, 4 parts of polyetherimide and 2 parts of McBride's acid ethanol solution;
[0039] (1) Weigh deionized water and modified maleic acid as needed, mix them, and keep stirring in a water bath at 60°C. After stirring and dissolving in the water bath, a first solution is obtained. Weigh the epoxy emulsifier and add it to the first solution. After stirring for 4 minutes, a second solution is obtained.
[0040] (2) Weigh polyetherimide and McLaughlin's acid ethanol solution as needed and place them in a water bath at 80°C for 1 hour. After the water bath is completed, add the first dissolving solution and the second dissolving solution, stir and react at room temperature for 10 minutes, and perform ultrasonic oscillation to remove bubbles to obtain a modified solution.
[0041] Among them, the preparation method of modified maleic acid is: water and corn starch are mixed in a mass ratio of 1:0.2 and added to a flask, and a slurry is obtained after stirring for 2 minutes, a catalyst is added and the stirring reaction is continued for 4 minutes, and after the stirring reaction is completed, the temperature is raised to 60°C and kept warm for 1 hour, and after the insulation reaction, a terminator accounting for 1% by mass is added dropwise, and then maleic acid accounting for 5% by mass is added, and the temperature is raised to 70°C, and the insulation reaction is carried out for 2 hours, and an equal amount of water in the above steps is added, and the reaction is stirred at room temperature for 2 minutes to obtain modified maleic acid.
[0042] Furthermore, the catalyst is a mixture of manganese sulfate and cuprous bromide, and the terminator is p-benzoquinone.
[0043] Furthermore, the cross-linking reaction temperature of the precursor and the carbohydrate is 200°C, the reaction time is 2h, and the sintering annealing temperature is 400°C.
[0044] Furthermore, in step S4, the temperature of the first carbonization treatment is 800°C, the heating rate is 2°C / min, and the temperature is kept for 2h.
[0045] Furthermore, in step S4, the curing treatment temperature is 1000°C, the heating rate is 30°C / min, and the temperature is kept for 1 hour.
[0046] Furthermore, in step S4, the temperature of the second carbonization treatment is 1200°C, the heating rate is 6°C / min, and the heat preservation time is 3h.
[0047] This embodiment also provides a coal-based hard carbon material, which is prepared by the preparation method of the coal-based hard carbon material.
[0048] Embodiment 2
[0049] The preparation method of the coal-based hard carbon material in this embodiment is basically the same as that in Example 1, except that the specific ratios of the raw materials used and the preparation methods of the modified solution and the modified coal powder raw materials are different. The specific ratios of the raw materials used to prepare the coal-based hard carbon material in this embodiment and the preparation method of the functional additives are as follows:
[0050] A method for preparing a coal-based hard carbon material comprises the following steps:
[0051] S1: After processing the coal raw material, a modified coal powder raw material is obtained;
[0052] S2: preparing a modified solution and setting it aside for use after the preparation is completed;
[0053] S3: mixing the modified coal powder raw material obtained by pretreatment in step S1 with the modified solution prepared in step S2, and obtaining a precursor after a mixing reaction;
[0054] S4: cross-linking the precursor obtained in step S3 with carbohydrates, obtaining an intermediate after sintering and annealing, and preparing a coal-based hard carbon material after the intermediate undergoes a first carbonization treatment, a curing treatment and a second carbonization treatment.
[0055] First, the treatment of the modified coal powder raw material in step S1 includes the following steps:
[0056] Step 1: Wash the coal raw material with water to obtain low-ash coal raw material, and then flatten and dry it after washing;
[0057] Step 2: After washing, the large coal raw materials are put into a jaw crusher for preliminary crushing. The coal raw materials after preliminary crushing are screened and crushed repeatedly, and then put into an impact crusher for fine crushing. Finally, they are crushed and screened to obtain coal powder with a particle size of less than 70 μm.
[0058] Step 3: Mix anhydrous ethanol and deionized water in a mass ratio of 1:2.7, add 17% by mass of coal powder and 4% by mass of methacryloyloxy functional silane to the mixed liquid, put the solid-liquid mixture into a magnetic stirrer, and stir at a speed of 1250r / min for 2.2min. After stirring, filter, wash and dry the slurry to obtain a filter cake, crush and screen the filter cake to obtain a modified coal powder raw material.
[0059] The preparation method of the modified solution in step S2 is as follows: the modified solution raw materials are composed of the following raw materials in parts by weight: 9 parts of deionized water, 6 parts of modified maleic acid, 5 parts of epoxy emulsifier, 5 parts of polyetherimide and 2.5 parts of McBride's acid ethanol solution;
[0060] (1) Weigh deionized water and modified maleic acid as needed, mix them, and keep stirring in a water bath at 65°C. After stirring and dissolving in the water bath, a first solution is obtained. Weigh the epoxy emulsifier and add it to the first solution. After stirring for 5 minutes, a second solution is obtained.
[0061] (2) Weigh polyetherimide and McLaughlin's acid ethanol solution as needed and place them in a water bath at 85°C for 1.2 hours. After the water bath is completed, add the first dissolving solution and the second dissolving solution, stir and react at room temperature for 12 minutes, and perform ultrasonic oscillation to remove bubbles to obtain a modified solution.
[0062] Among them, the preparation method of modified maleic acid is: water and corn starch are mixed in a mass ratio of 1:0.25 and added to a flask, and a slurry is obtained after stirring for 2.5 minutes, a catalyst is added and the stirring reaction is continued for 4.5 minutes, and after the stirring reaction is completed, the temperature is raised to 62°C and kept warm for 1.2 hours, and after the insulation reaction, a terminator with a mass percentage of 1.2% is added dropwise, and then maleic acid with a mass percentage of 6% is added, and the temperature is raised to 72°C, and the insulation reaction is carried out for 2.2 hours, and an equal amount of water in the above steps is added, and the reaction is stirred at room temperature for 2.5 minutes to obtain modified maleic acid.
[0063] Furthermore, the catalyst is cuprous bromide and the terminator is chlorobenzoquinone.
[0064] Furthermore, the cross-linking reaction temperature of the precursor and the carbohydrate is 250°C, the reaction time is 5h, and the sintering annealing temperature is 500°C.
[0065] Furthermore, in step S4, the temperature of the first carbonization treatment is 900°C, the heating rate is 3°C / min, and the heat preservation time is 2.5h.
[0066] Furthermore, in step S4, the curing treatment temperature is 1100°C, the heating rate is 35°C / min, and the heat preservation time is 1.2h.
[0067] Furthermore, in step S4, the temperature of the second carbonization treatment is 1400°C, the heating rate is 8°C / min, and the heat preservation time is 4h.
[0068] This embodiment also provides a coal-based hard carbon material, which is prepared by the preparation method of the coal-based hard carbon material.
[0069] Embodiment 3
[0070] The preparation method of the coal-based hard carbon material in this embodiment is basically the same as that in Example 1, except that the specific ratios of the raw materials used and the preparation methods of the modified solution and the modified coal powder raw materials are different. The specific ratios of the raw materials used to prepare the coal-based hard carbon material in this embodiment and the preparation method of the functional additives are as follows:
[0071] A method for preparing a coal-based hard carbon material comprises the following steps:
[0072] S1: After processing the coal raw material, a modified coal powder raw material is obtained;
[0073] S2: preparing a modified solution and setting it aside for use after the preparation is completed;
[0074] S3: mixing the modified coal powder raw material obtained by pretreatment in step S1 with the modified solution prepared in step S2, and obtaining a precursor after a mixing reaction;
[0075] S4: cross-linking the precursor obtained in step S3 with carbohydrates, obtaining an intermediate after sintering and annealing, and preparing a coal-based hard carbon material after the intermediate undergoes a first carbonization treatment, a curing treatment and a second carbonization treatment.
[0076] First, the treatment of the modified coal powder raw material in step S1 includes the following steps:
[0077] Step 1: Wash the coal raw material with water to obtain low-ash coal raw material, and then flatten and dry it after washing;
[0078] Step 2: After washing, the large coal raw materials are put into a jaw crusher for preliminary crushing. The coal raw materials after preliminary crushing are screened and crushed repeatedly, and then put into an impact crusher for fine crushing. Finally, they are crushed and screened to obtain coal powder with a particle size of less than 70 μm.
[0079] Step 3: Mix anhydrous ethanol and deionized water in a mass ratio of 1:3, add 20% by mass of coal powder and 5% by mass of methacryloyloxy functional silane to the mixed liquid, put the solid-liquid mixture into a magnetic stirrer, and stir at a speed of 1300 r / min for 2.5 min. After stirring, filter, wash and dry the slurry to obtain a filter cake, crush the filter cake, and screen it to obtain a modified coal powder raw material.
[0080] The modified solution preparation method in step S2 is as follows: the modified solution raw materials are composed of the following raw materials in parts by weight: 10 parts of deionized water, 7 parts of modified maleic acid, 6 parts of epoxy emulsifier, 6 parts of polyetherimide and 3 parts of McBride's acid ethanol solution;
[0081] (1) Weigh deionized water and modified maleic acid as needed, mix them, and keep stirring in a water bath at 70°C. After stirring and dissolving in the water bath, a first solution is obtained. Weigh the epoxy emulsifier and add it to the first solution. After stirring for 6 minutes, a second solution is obtained.
[0082] (2) Weigh polyetherimide and McLaughlin's acid ethanol solution as needed and place them in a 90°C water bath for 1.5 hours. After the water bath is completed, add the first dissolving solution and the second dissolving solution, stir and react at room temperature for 15 minutes, and perform ultrasonic oscillation to remove bubbles to obtain a modified solution.
[0083] Among them, the preparation method of modified maleic acid is: water and corn starch are mixed in a mass ratio of 1:0.3 and added to a flask, and a slurry is obtained after stirring for 3 minutes, a catalyst is added and the stirring reaction is continued for 5 minutes, and after the stirring reaction is completed, the temperature is raised to 65°C and kept warm for 1.5 hours, and after the insulation reaction, a terminator with a mass percentage of 1.5% is added dropwise, and then maleic acid with a mass percentage of 7% is added, and the temperature is raised to 75°C, and the insulation reaction is carried out for 2.5 hours, and an equal amount of water in the above steps is added, and the reaction is stirred at room temperature for 3 minutes to obtain modified maleic acid.
[0084] Furthermore, the catalyst is manganese dioxide, and the terminator is p-benzoquinone.
[0085] Furthermore, the cross-linking reaction temperature of the precursor and the carbohydrate is 300°C, the reaction time is 10h, and the sintering annealing temperature is 550°C.
[0086] Furthermore, in step S4, the temperature of the first carbonization treatment is 1100°C, the heating rate is 5°C / min, and the temperature is kept for 3 hours.
[0087] Furthermore, in step S4, the curing treatment temperature is 1300°C, the heating rate is 40°C / min, and the heat preservation time is 1.5h.
[0088] Furthermore, in step S4, the temperature of the second carbonization treatment is 1600°C, the heating rate is 10°C / min, and the heat preservation time is 5h.
[0089] This embodiment also provides a coal-based hard carbon material, which is prepared by the preparation method of the coal-based hard carbon material.
[0090] Comparative Example 1: The difference between this embodiment and embodiment 1 is that this embodiment uses an equal amount of coal powder raw material instead of modified coal powder raw material.
[0091] Comparative Example 2: The difference between this embodiment and embodiment 1 is that the first carbonization treatment is not performed in this embodiment.
[0092] Comparative Example 3: The difference between this embodiment and embodiment 1 is that in this embodiment, a McBride's acid ethanol solution is added when modifying the solution additive.
[0093] Comparative Example 4: The difference between this example and Example 1 is that in this example, an equal amount of maleic acid is used to replace the modified solution.
[0094] Performance test: The relevant properties of the coal-based hard carbon material samples provided in Examples 1-3 and Comparative Examples 1-4 were tested respectively, and the obtained test data were recorded in the following table:
[0095]
[0096] By comparing and analyzing the relevant data in the table, it can be seen that the coal-based hard carbon material prepared by the present invention not only has good first discharge specific capacity performance, but also has excellent specific surface area performance. This shows that the coal-based hard carbon material and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.
[0097] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0098] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a coal-based hard carbon material, characterized in that: The following steps are involved: S1: After processing the coal raw material, a modified coal powder raw material is obtained; S2: preparing a modified solution and setting it aside for use after the preparation is completed; S3: mixing the modified coal powder raw material obtained in step S1 with the modified solution prepared in step S2, and obtaining a precursor after a mixing reaction; S4: cross-linking the precursor obtained in step S3 with carbohydrates, obtaining an intermediate after sintering and annealing, and preparing a coal-based hard carbon material after the intermediate undergoes a first carbonization treatment, a curing treatment and a second carbonization treatment; The processing of the modified pulverized coal raw material in step S1 comprises the following steps: Step 1: Wash the coal raw material with water to obtain low-ash coal raw material, and then flatten and dry it after washing; Step 2: After washing, the large coal raw materials are put into a jaw crusher for preliminary crushing. The coal raw materials after preliminary crushing are screened and crushed repeatedly, and then put into an impact crusher for fine crushing. Finally, they are crushed and screened to obtain coal powder with a particle size of less than 70 μm. Step 3: Mix anhydrous ethanol and deionized water in a mass ratio of 1:2.5-3, add 15-20% by mass of coal powder and 3-5% by mass of methacryloyloxy functional silane to the mixed liquid, put the solid-liquid mixture into a magnetic stirrer, and stir it at a speed of 1200-1300r / min for 2-2.5min. After stirring, filter, wash and dry the slurry to obtain a filter cake, crush the filter cake, and screen it to obtain a modified coal powder raw material.
2. The method for preparing a coal-based hard carbon material according to claim 1, characterized in that: The modified solution preparation method in step S2 is as follows: the modified solution raw materials are composed of the following raw materials in parts by weight: 8-10 parts of deionized water, 5-7 parts of modified maleic acid, 4-6 parts of epoxy emulsifier, 4-6 parts of polyetherimide and 2-3 parts of McBride's acid ethanol solution; (1) Weigh deionized water and modified maleic acid as needed, mix them, and keep stirring in a water bath at 60-70°C. After stirring and dissolving in the water bath, a first solution is obtained. Weigh the epoxy emulsifier and add it to the first solution. After continuous stirring for 4-6 minutes, a second solution is obtained. (2) Weigh the polyetherimide and McLaughlin's acid ethanol solution as needed and place them in a water bath at 80-90°C for 1-1.5 hours. After the water bath is completed, add the first dissolving solution and the second dissolving solution, stir and react at room temperature for 10-15 minutes, and perform ultrasonic vibration to remove bubbles to obtain a modified solution.
3. The method for preparing a coal-based hard carbon material according to claim 2, characterized in that: The preparation method of the modified maleic acid is as follows: water and corn starch are mixed in a mass ratio of 1:0.2-0.3 and added into a flask, and a slurry is obtained after stirring for 2-3 minutes, a catalyst is added, and the stirring reaction is continued for 4-5 minutes, and the temperature is raised to 60-65° C. and kept warm for 1-1.5 hours after the stirring reaction is completed, and a terminator accounting for 1-1.5% by mass is added dropwise after the reaction, and then maleic acid accounting for 5-7% by mass is added, and the temperature is raised to 70-75° C., and the reaction is kept warm for 2-2.5 hours, and an equal amount of water in the above steps is added, and the reaction is stirred at room temperature for 2-3 minutes to obtain the modified maleic acid.
4. The method for preparing a coal-based hard carbon material according to claim 3, characterized in that: The catalyst is one or more combinations of manganese sulfate, cuprous bromide and manganese dioxide, and the terminator is any one of p-benzoquinone and tetrachlorobenzoquinone.
5. The method for preparing a coal-based hard carbon material according to claim 1, characterized in that: The cross-linking reaction temperature of the precursor and carbohydrate is 200-300°C, the reaction time is 2-10h, and the sintering annealing temperature is 400-550°C.
6. The method for preparing a coal-based hard carbon material according to claim 1, characterized in that: The temperature of the first carbonization treatment in step S4 is 800-1100°C, the heating rate is 2-5°C / min, and the temperature is kept for 2-3h.
7. The method for preparing a coal-based hard carbon material according to claim 1, characterized in that: The curing temperature in step S4 is 1000-1300°C, the heating rate is 30-40°C / min, and the temperature is kept for 1-1.5h.
8. The method for preparing a coal-based hard carbon material according to claim 1, characterized in that: The temperature of the second carbonization treatment in step S4 is 1200-1600°C, the heating rate is 6-10°C / min, and the heat preservation is 3-5h.
9. A coal-based hard carbon material, characterized in that: The coal-based hard carbon material is prepared by the preparation method of any one of claims 1 to 8.
Citation Information
Patent Citations
Coal-based hard carbon as well as preparation method and application thereof
CN118004996A
Coal-based hard carbon negative electrode material and preparation method and application thereof
CN118598120A